Paroxysmal Sympathetic Hyperactivity Syndrome (Review) - L. M. Tsentsiper; I. S. Terekhov; O. A. Shevelev; M. V. Petrova; A. N. Kondratiev (Общая реаниматология, 2022)
Paroxysmal sympathetic hyperactivity (PSH) is one of the complications of acute severe brain injuries (traumatic brain injury, intracranial hemorrhage, ischemia, and posthypoxic conditions) in both adults and children. Its high incidence and severe sequelae including organ dysfunction, infectious complications, impaired blood supply to organs and tissues associate with increased disability and mortality. The choice of effective therapy can be challenging because of multifaceted manifestations, diagnostic diﬃculties, and lack of a clear understanding of the pathophysiology of PSH. Currently, there are various local and international treatment strategies for PSH.The aim of the review is to summarize clinical and scientific research data on diagnosis and treatment of PSH to aid in the selection of an effective therapy.Material and methods. Web of Science, Scopus and RSCI databases were employed to select 80 sources containing relevant clinical and research data on the subject of this review.Results. The key principles of diagnosis and treatment of paroxysmal sympathetic hyperactivity have been reviewed. The current views on etiology and pathogenesis of paroxysmal sympathetic hyperactivity development were outlined. The clinical data concerning complications and sequelae of paroxysmal sympathetic hyperactivity were analyzed. We conclude the review with a discussion of current methods of the syndrome prevention.Conclusion. Preventing PSH and its adequate and prompt treatment could help avoid the abnormal pathway development following a severe brain injury, reduce its negative consequences and rate of complications, along with the duration of mechanical lung ventilation, patient's stay in ICU, disability and mortality rates. Careful selection of pathogenetic, symptomatic and supportive therapy significantly improves the rehabilitation potential of patients.